STRATEGIC COMMUNICATION CONTINUES TO BE STRONGLY INSTRUMENTAL: RESULTS OF A LONG-TERM STUDY OF PR PRACTICES IN AUSTRIA - Peter Dietrich,Christoph Hauser,Sascha Leiber,Mark Romanelli (Fonseca, Journal of Communication, 2023)
Over the last four decades, the PR industry tried hard to develop from an operational practice into a full strategic management function. Analyzing the submissions for the Austrian-PR-State-Award (1984-2020) shows no significant changes in the perception and treatment of PR problems in this period. A symbolicinterpretive mode is more often practiced than a dialogue-oriented management mode. The main focus is on gaining internal influence, and improving the actual performance is neglected. Hence, due to this imbalance, the possibility of professionalization efforts through a mutually reinforcing dynamic of increase between performance and influence cannot be fully exploited.